1994
DOI: 10.1159/000168723
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Nonocclusive Mesenteric Infarction during Continuous Ambulatory Peritoneal Dialysis

Abstract: An unexpected case of nonocclusive mesenteric infarction in a patient on continuous ambulatory peritoneal dialysis is described. The common clinical finding in this entity is a low cardiac output state or even circulatory collapse. Nonocclusive mesenteric infarction has been reported very rarely during continuous ambulatory peritoneal dialysis, and only in the setting of cardiac dysfunction or prolonged hypotension. The current patient had none of the typical features commonly described in the clinical setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In recent years, non-occlusive mesenteric ischemia (NOMI) has become increasingly recognized as a highly dangerous complication in both hemodialysis [1,2,3,4,5,6,7,8,9,10,11,12] and peritoneal dialysis patients, young and old alike [13,14,15]. Undoubtedly, NOMI is seen far more often in hemodialysis patients, with intradialytic hypotension being the major precipitating factor behind the development of NOMI among these patients [1, 2,4,5,6, 11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, non-occlusive mesenteric ischemia (NOMI) has become increasingly recognized as a highly dangerous complication in both hemodialysis [1,2,3,4,5,6,7,8,9,10,11,12] and peritoneal dialysis patients, young and old alike [13,14,15]. Undoubtedly, NOMI is seen far more often in hemodialysis patients, with intradialytic hypotension being the major precipitating factor behind the development of NOMI among these patients [1, 2,4,5,6, 11].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Besides the traditional risk factors, CKD patients are more prone for vascular calcification[ 3 ] and increasing risk of ischemia because of the use of erythropoietin. [ 4 5 ] Erythropoietin has also direct vasopressor effect on mesenteric blood vessels. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…This increased hematocrit leads to hyperviscosity and consequently a low flow state. The mechanism just described can be reproduced through the use of recombinant human erythropoietin (rHuEPO) (23,24). Studies in an in vitro and ex vivo model demonstrated that EPO also has a direct vasopressor effect on small mesenteric resistance vessels (25).…”
Section: Discussionmentioning
confidence: 99%